2014
DOI: 10.1016/j.ausmj.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

So Many Things to Do! How Multitasking Affects Memory and Attitude for Product and Brand Placements

Abstract: The majority of current product placement research is predicated on a cinema setting and assumes a rather captive audience. Little is known, about the effect of audience multitasking on product placements. As multitasking activity is most prevalent in the home, an understanding of this activity is critical to developing product placement techniques. This initial study investigates the effects of multitasking on both subtle and prominent product placements. The results indicate that less familiar, prominently p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…The results for BRc also support the findings of previous studies about IGA in which relative differences were found according to placement prominence (Nelson, 2002;Cauberghe & DePelsmacker, 2010;Gunawardena & Waiguny, 2014). The difference between BRc for prominent and subtle placements is summarized in Figure 3.…”
Section: Brand Recall (Brc)supporting
confidence: 88%
See 3 more Smart Citations
“…The results for BRc also support the findings of previous studies about IGA in which relative differences were found according to placement prominence (Nelson, 2002;Cauberghe & DePelsmacker, 2010;Gunawardena & Waiguny, 2014). The difference between BRc for prominent and subtle placements is summarized in Figure 3.…”
Section: Brand Recall (Brc)supporting
confidence: 88%
“…In high cognitive load condition, since there is limited capacity for the working memory, highly visible brands have a higher chance to be recognized by the player, thus the memory. As verified by Gunawardena and Waiguny (2014)subtle placements within the peripheral area of the movie will give rise to a greater decrease in recall and recognition than the prominent placements. On the other hand, subtle placement is not easy to discover in natural setting.…”
Section: The Moderating Impact Of Placement Prominence On Cognitive Loadmentioning
confidence: 83%
See 2 more Smart Citations
“…The main carriers for product placement are mass media and entertainment such as movies, serials, TV shows, video games, books, or theater [83]. The modern consumer of the entertainment mass media in everyday life rarely focuses all its attention on the content transmitted in the mass media [84].…”
Section: Product and Brand Placement: Moviementioning
confidence: 99%